Socialization and Evaluation of the BLM Program for Penataban Giri Banyuwangi Village - Dedi, Mohamad (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
A good and healthy environment is very important in supporting human survival. Settlement drainage is a facility or infrastructure in settlements to drain rainwater from one place to another. The wastewater distribution system is a series of water structures that function to reduce or dispose of wastewater from an area or land, both households and industrial areas. The KOTAKU Program (City Without Slums) BLM Program for Penataban Giri Banyuwangi Village has been completed, namely the construction of drainage facilities, toilets, and beautification. The hope is that after the construction of some of these facilities can help the level of cleanliness and quality of a healthy environment for the community. Hopefully in the future the community can maintain the local wisdom values ​​of environmental preservation in the Penataban Village, namely the value of environmental adaptation, the value of responsibility, the value of environmental awareness, and the value of cooperation. The values ​​of local wisdom as an effort to maintain the environment in Penataban Village are reflected in the activities of residents in maintaining drainage channels for waste water management, maintaining environmental cleanliness and the spirit of community cooperation to beautify and preserve the surrounding.